Effect of pore fluid on ultrasonic S-wave attenuation in partially saturated tight rocks. (November 2021) - Ma, Rupeng; Ba, Jing; Lebedev, Maxim; Gurevich, Boris; Sun, Yongyang
Abstract: S-wave attenuation in porous media is affected by the presence and properties of saturating fluids. We measured the ultrasonic S-wave velocities of three types of tight rocks (siltstone, dolomite, and sandstone) under partial fluid saturation conditions using the pulse-transmission technique. The S-wave attenuation is estimated by the centroid frequency shift and spectral-ratio methods. The fluid-saturated test results show that the attenuation of most water-saturated dolomites is stronger than that of gas- or oil-saturated dolomites, whereas no apparent relationship exists between attenuation and fluid type in siltstone. The attenuation of siltstone and dolomite increases with increasing porosity and permeability, as well as with clay content for siltstone with clay contents less than 6%. The maximum attenuation of rocks partially saturated with gas and water occurs at high water saturation (55%–100%) in most siltstones. The attenuation of most dolomites shows an increasing trend with water saturation, but remains nearly unchanged in partially saturated sandstone. The attenuation of rocks partially saturated with oil and water is strongest at the partial saturation state in siltstone, but remains essentially constant with water saturation in dolomite. A squirt flow model is used to predict the S-wave attenuation of the fluid-saturated sample. Based on rock property and microstructure analyses, wave attenuation in the fluid-saturated rocks measured in this study can be explained by squirt flow mechanisms and the scattering effect owing to heterogeneities of water patches and grain clusters.